SPINDLE THERMAL EVALUATION THERMAL ON REALIABILITY TEST OF NUMERICAL CONTROLLED LATHE - Suryaningrat, Albertus Rianto; -, Nasril -; Ningsih, Marsetiayu; Nurhidayat, Yanyan (Majalah Ilmiah Pengkajian Industri, 2019)
In the process of designing and manufacturing of CNC machine tools, reliability testing is needed to determine the reliability of the main component design and sub assembly. The precision of machine tools is greatly influenced by the temperature generated when the machine tool operates, both which arise from friction and overload.Evaluation of spindle axis errors caused by thermal distortion of the spindle bearing is based on ISO 230-3: 2007, ISO 10791-10: 2001 and ISO 13041-8: 2004. Temperature measurement at several measuring points on the spindle head to determine the increase in temperature on the main spindle bearing when getting more load or cutting process.The evaluation results showed that spindle erroneous error with a temperature increase in the spindle head was 16.3 oC by 13 um with no loading, while with loading 71.9 um with a temperature increase of 18.0 oC.